Major technological advances will enhance Australian donor‐recipient matching and improve transplant outcomes. Issue 1 (24th January 2023) - Hiho, Steven; Levvey, Bronwyn; Holdsworth, Rhonda; Sullivan, Lucy; Westall, Glen; Snell, Greg
Abstract: In recent times, numerous and significant technological and supportive changes have taken place in Australian transplantation. These changes are often deployed without the wider clinical community having a full understanding of what has brought about these changes and the impacts they have. Here, we aim to clarify the reasoning behind these changes and shed light on potential future endeavours to improve patient outcomes.